MAMANGAN MINANGKABAU (Sebuah Kajian Semiotik) - Lindawati Lindawati (Universitas Andalas, 2012)
This article exposes meanings, functions, and contexts of Minangkabau mamangans. Nature that inspirited the forms and social relationships on this mamangan are also described. With antropolinguistics approach, this analysis aims culture and language systems mapping to see the social system relevancies.There are anomalous and deviations on the mamangan. Several anomalous mamangans are formed from physical phenomenon and the deviations can be seen on diversion of form and meaning. So, mamangan functions and meanings can be explained from the context.